Personalized Technology to Support Older Adults With and Without Cognitive Impairment Living at Home - Kerssens, Chantal (Am J Alzheimers Dis Other Demen, 2015)
Although persons with dementia (PWD) and their family caregivers need in-home support for common neuropsychiatric symptoms (NPS), few if any assistive technologies are available to help manage NPS. This implementation study tested the feasibility and adoption of a touch screen technology, the Companion, which delivers psychosocial, nondrug interventions to PWD in their home to address individual NPS and needs. Interventions were personalized and delivered in home for a minimum of 3 weeks. Postintervention measures indicated the technology was easy to use, significantly facilitated meaningful and positive engagement, and simplified caregivers’ daily lives. Although intervention goals were met, caregivers had high expectations of their loved one’s ability to regain independence. Care recipients used the system independently but were limited by cognitive and physical impairments. We conclude the Companion can help manage NPS and offer caregiver respite at home. These data provide important guidance for design and deployment of care technology for the home.